Concurrent Immediate Reference Counting - Jung, Jaehwang; Kim, Jeonghyeon; Parkinson, Matthew J.; Kang, Jeehoon (PACM PL, 2024)
Memory management for optimistic concurrency in unmanaged programming languages is challenging. Safe memory reclamation (SMR) algorithms help address this, but they are difficult to use correctly. Automatic reference counting provides a simpler interface, but it has been less efficient than SMR algorithms. Recently, there has been a push to apply the optimizations used in garbage collectors for managed languages to elide reference count updates from local references. Notably, Fast Reference Counter, OrcGC, and Concurrent Deferred Reference Counting use SMR algorithms to protect local references by deferring decrements or reclamation. While they show a significant performance improvement, their use of deferral may result in growing memory usage due to slow reclamation of linked structures, and suboptimal performance in update-heavy workloads. We present Concurrent Immediate Reference Counting (CIRC), a new combination of SMR algorithms with reference counting. CIRC employs deferral like other modern methods, but it avoids their problems with novel algorithms for (1) immediately reclaiming linked structures recursively by tracking the reachability of each object, and (2) applying decrements immediately and deferring only the reclamation. Our experiments show that CIRC’s memory usage does not grow over time and is only slightly higher than the underlying SMR. Moreover, CIRC further narrows the performance gap between the underlying SMR, positioning it as a promising solution to safe automatic memory management for highly concurrent data structures in unmanaged languages.